Green lacewings (Neuroptera: Chrysopidae) of Yakutia and Magadan Region (Russia), and the northern limit of the range of the family - V.N.Makarkin; V.A.Krivokhatsky; A.I. Averеnsky (Кавказский энтомологический бюллетень, 2016)
Faunistic data on eight species of Chrysopidae (Neuroptera) from Republic of Sakha (Yakutia) and Magadan Region are reported. Chrysopa dasyptera McLachlan, 1872 is newly recorded from these regions, and Ch. abbreviata Curtis, 1834 from Yakutia. The northern limit of the range of Chrysopidae is discussed. It is noted that this limit is shifted much further south in Asia (especially in the northeast) than in Europe and North America.